Screening for depression among first‐visit psychiatric patients: Comparison of different scoring methods for the Center for Epidemiologic Studies Depression Scale using receiver operating characteristic analyses - FURUKAWA, TOSHIAKI; ANRAKU, KAZUTAKA; HIROE, TAKAHIRO; TAKAHASHI, KIYOSHI; KITAMURA, TOSHINORI; HIRAI, TOSHIYUKI; TAKAHASHI, KIYOHISA; IIDA, MAKOTO (Psychiatry and clinical neurosciences, 1997)
The present paper aims to compare the ability of eight scoring methods for the Center for Epidemiologic Studies Depression Scale (CES‐D), one of the most widely used self‐report inventories for depression, to screen for a major depressive episode. The subjects were 591 patients who constituted representative samples of the first‐visit patients to 23 psychiatric hospitals and clinics all over Japan. The criterion diagnoses were given by a semi‐structured interview with established inter‐rater reliability. The eight alternative scoring methods included the conventional Likert method, which gives the weights 0,1,2 and 3 to the four anchor points of the CES‐D; the presence method, which gives the weights 0, 1, 1 and 1, respectively; the GHQ method, which gives the weights 0, 0, 1 and 1, respectively; the persistence method, which gives the weights 0, 0, 0 and 1, respectively; 10‐item version, 5‐item version, single‐item version and the algorithmic method. On the basis of the receiver operating characteristic (ROC) analyses, it was found that the traditional Likert scoring method of the full CES‐D performed best in detecting major depressive episodes among first‐visit psychiatric patients. The presence method, the GHQ method and the 10‐item version appeared to have a similar ability. The persistence method, the 5‐item version and the single‐item version resulted in significantly worse performance.